'Her heart knows my heart for a brief moment': Mediated affect and utopian impulse in Many Moons (2011) by Alice Birch. (1st September 2018) - Escoda, Clara
This article reads Many Moons (2011), by British playwright Alice Birch, from the point of view of the 'affective turn' that has recently taken place in the humanities and social sciences. While acknowledging recent critiques on affect theory, this article considers its political potential and analyses two of the stratgies through which Many Moons seeks to interrupt the 'mediated affect[s]' of consumer capitalist societies. These strategies, which can be considered 'utopian performatives', take the form of moments of 'radical naivety'on the part of the characters, and of the dramatization of a face-to-face encounter between two characters: Meg and Robert. The article finally explores the extent to which these strategies seek to invite spectators to break with the dominant 'distribution of the sensible', ultimately contributing to create 'a new affective topology of the possible'.